(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
With the rise of technology and the growing internet usage, children learning languages is slowly changing. The traditional audio-lingual teaching methods of foreign language teaching using textbooks and drills is a phenomenon of the past. Interactive apps, voice recognition games, animated stories, as well as virtual exchanges, now teach young learners to speak in new ways. For primary education students, vocabulary lessons include dynamic resources that immerse learners in languages. During thoughtfully crafted multimedia sessions, children’s self-expression is developed so that they internalize conversational speech, pronunciation, intonation, and even more. As a result, learners become more captivated and instruction becomes more effective while children acquire language more authentically as they do with first languages. The aim of this paper is to analyze the impact of multimedia in speaking skills development.